2023
DOI: 10.3390/cancers15092432
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms and Future Opportunities for the Management of Radiation Necrosis in Patients Treated for Brain Metastases in the Era of Immunotherapy

Abstract: Radiation necrosis, also known as treatment-induced necrosis, has emerged as an important adverse effect following stereotactic radiotherapy (SRS) for brain metastases. The improved survival of patients with brain metastases and increased use of combined systemic therapy and SRS have contributed to a growing incidence of necrosis. The cyclic GMP-AMP (cGAMP) synthase (cGAS) and stimulator of interferon genes (STING) pathway (cGAS-STING) represents a key biological mechanism linking radiation-induced DNA damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 190 publications
0
0
0
Order By: Relevance
“…Pathological examination also indicated RN. Numerous previous studies have reported that SRT combined with immunotherapy increased the risk of radiation necrosis ( 31 , 36 , 37 ). Therefore, the concern regarding the potential risk of RN following SRT combined with PD-L1 immunotherapy has increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological examination also indicated RN. Numerous previous studies have reported that SRT combined with immunotherapy increased the risk of radiation necrosis ( 31 , 36 , 37 ). Therefore, the concern regarding the potential risk of RN following SRT combined with PD-L1 immunotherapy has increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the penumbra around the necrotic nucleus, astrocytes, microglia and oligodendrocytes produce factors (e.g. VEGF) that promote cytokine release and increase the permeability of the BBB ( 37 ). However, the mechanisms by which the combination of anti-PD-L1 and radiotherapy promotes RN are still unclear.…”
Section: Discussionmentioning
confidence: 99%